Challenges to Inclusive Growth : A Poverty and Equity Assessment of Djibouti - World Bank Group (World Bank, Washington, DC, 2019)
The objective of this report is to present a snapshot of the welfare landscape in Djibouti that will help stakeholders understand poverty’s determinants. Exploiting data from the 2017 household expenditure survey, as well as administrative and geospatial data, it provides a detailed analysis of poverty in the country, its strong link to labor market outcomes, and the differential access to opportunities between urban and rural areas. Djibouti has recently experienced a period of unprecedented economic development, allowing it to grow its economy by an average of 7 percent per year between 2013 and 2016. This report shows that over a fifth of the Djiboutian population continues to live in extreme poverty and that the country has high levels of inequality, ranking 71 out of 95 countries with information on Gini available circa 2015. The report also focuses on the nexus of (monetary) poverty and the labor market. With a dual labor market, divided between the public sector and informality, a large share of the population—especially those who are vulnerable—continue to face high risks, as they have neither the skills nor opportunities to lift themselves out of poverty. Djibouti needs to double its efforts in pursuing an inclusive growth strategy. This strategy will need to be sustained by a strong labor market that allows individuals to capitalize on recent investments in education and closes the gaps in human capital across all groups of the population.